(untitled) (E-Jurnal Ekonomi Pembangunan, 2025)
During the process of producing salt, some farmers will concentrate on factors that have an impact on production. As a result, the focus of this study will be on determining the factors that influence salt production. Based on the responses to a survey via questionnaire, observations, and in-person interviews with 62 participants, the research data source was compiled. The kind of examination procedure applied in this study is utilizing a quantitative investigation strategy with different relapse types. This study demonstrates that farmers in Kusamba Village’s salt production levels are correlated with capital, labor, and land area. Keyword: capital, Labor, Land Area, Production Rate